Evaluation of the efficacy of clear aligners in mandibular advancement and their effect on mandibular trabecular structures using fractal dimension analysis - Nurver Karslı; Merve Gonca; Gizem Mine Türksever; Nesrin Atasaral Beyaz (BMC Oral Health)
Abstract Background The objective of this study was to evaluate the efficacy of the mandibular advancement protocol (MA) with clear aligners in the treatment of skeletal Class II malocclusion and to assess their effect on the mandibular trabecular structure using fractal dimension analysis (FD-A) on panoramic radiographs. Methods The study included panoramic and cephalometric radiographs of 20 patients (treatment group, mean age: 11.7 ± 0.8 years; 9 girls, 11 boys) with Class II malocclusion, treated with the mandibular advancement protocol (MA) using clear aligners. The radiographs were obtained before treatment (T0) and following the MA phase (T1). Additionally, panoramic radiographs of 20 control subjects who had undergone no orthodontic treatment (control group, mean age: 11.7 ± 0.9 years; 9 girls, 11 boys) were analyzed. The fractal dimension values of the mandibular trabecular structures in the condylar, gonial, and corpus regions were evaluated for both groups. Statistical analyses were performed using paired t-test and independent samples t-test for parametric data, and Wilcoxon test and Mann-Whitney U test for non-parametric data. Statistical significance was set at P < 0.05. Results The treatment applied using MA with aligners resulted in significant decreases in SNA (P < 0.05), ANB (P < 0.05), 1-NA (P < 0.001), overjet (P < 0.001), and overbite (P < 0.01). Conversely, significant increases were observed in S-Go (P < 0.01) and 1-NB (P < 0.05) parameters. The FD-A changes between T0 and T1 indicated that the observed increases in the right and left condylar processes, the left gonial region, and the left mandibular corpus were not statistically significant in the treatment group (P > 0.05). The comparison of the FD-A results between the groups revealed no statistically significant differences (P > 0.05). Conclusions The FD-A results revealed no significant alterations in the trabeculation of the mandibular bone in the treatment group. These findings suggest that MA treatment with aligners primarily contributes to dental correction rather than inducing changes in the skeletal structure and trabeculation of the mandibular bone.